Trabecular morphology of humeri with the Supratrochlear Aperture (STA) and characteristics of the tissue crossing the STA - Pillay, Shayla Kohrika (My University, 2020)
The supratrochlear aperture (STA) of the humerus is the opening that forms when the septum separating the coronoid and olecranon fossae is perforated. While the aetiology is unknown, one study suggested that articulation of the ulnar coronoid process with its respective fossa may cause septal resorption to form the STA. Conversely, recent findings implicated a longer olecranon process. This study aimed to test the validity of these two suggestions using cadaveric samples as well as to investigate the differences in the internal bone morphology in individuals with and without the STA to determine whether the STA may form due to incomplete bone remodelling. Bone samples were taken from 30 cadavers with equal numbers in the STA category, controls with a thick (opaque) septum or with a thin (translucent) septum and fixed in paraformaldehyde, decalcified and processed for histological assessment. The posterior aspects of the samples were marked to differentiate the coronoid (anterior) from the olecranon (posterior) side. Sections (5µm thick) were cut with a microtome and stained with H&E for morphological assessment, Rapid One-Step Mallory Heidenhain to identify the connective tissue structure and Picrosirius Red to analyse the collagen types found in the section. Images of the sections were captured using the Olympus BX63 Fluorescence Microscope. Area, length and width measurements were taken to measure bone resorption. Area measurements of the connective tissue on translucent sections were taken on anterior and posterior surfaces. A gradient was plotted onto each section, for the opaque and translucent septum sections to measure the difference in density of bone from anterior to posterior. Additionally, 30 paired humeri belonging to females of African descent between the ages of 18 and 50 years were selected from the Raymond A Dart Collection of Human Skeletons. These comprised of 15 bilateral humeri with the STA and 15 bilateral humeri without the STA. Humeri were scanned using a Nikon XTH 225/320 LC dual-source industrial Micro-CT scanner. Measurements from the reconstructed images included the bicondylar breadth, bone to total volume (BV/TV), trabecular number (TbN), thickness (TbTh) and spacing (TbSp). These measurements aided in determining whether there were differences in bone volume by STA status. Histological analysis showed increased occurrence of connective tissue found on the posterior aspect of translucent septum sections compared to that on the anterior aspect. iv Similarly, there was an increased percentage of bone found on the anterior aspect compared to the posterior aspect of the section in translucent septum sections. Significant differences were found in the BV/TV, TbN and TbSp, in the proximal region on the right in humeri with the STA. Therefore septal resorption occurs primarily from the posterior aspect and the differences in trabecular bone may have resulted from the overactivity of osteoclasts
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Anatomical Sciences, University of the Witwatersrand, Johannesburg, 2020